Evaluation Of Force Required For Retrieval Of Pre-cementation Silanized Post By Pull Out Test And Electron Microscopic Study Of Surface Changes Of Retrieved Posts : An Original Research - Sourav Bhattacharya, Niladri Maiti , Aditya Mitra, Anirban Bhattacharyya, Asim Bikash Maity, Prithwi Bhattacharyy (South Eastern European Journal of Public Health, 2025)
Introduction: The aim of the study was to test retentive forces of different adhesive systems after cementation of glass-fiber posts with or without prior silanization of the post by using a pullout test and scanning electron microscope (SEM) observation to detect the mode of failure. Methods: Forty roots were randomly divided into 6 experimental and 2 control groups: Multilink Speed( Group IA ), Multilink Speed + silane (Group IB), Voco Rebulda DC (Group IIA), Voco Rebulda DC + silane (Group IIB), ReluxU200 (Group IIIA), ReluxU200 + silane (Group IIIB), negative control (NEG-CON), and positive control (POS-CON). Tanex posts were placed in the experimental groups (each n = 5) by using an adhesive resin with or without prior silanization. NEG-CON received uncemented posts (n = 5); POS-CON received an active screw post with an adhesive (n = 5). All samples were subjected to a pullout test in a universal mechanical testing machine for pullout tests and SEM to assess the fiber posts and the roots after the tests. Results: Mean failure load values for each ground Group-I-A 11.39Mpa, Group-I-B 11.40Mpa. GRP II-A 14.60N, GRP II-B 14.5N, GRP III-A 13.30 N, GRP III-B 13.80N. The mean failure load (bond strength) of Group-I-A was lower than that of Group-I-B but t-test showed that there was no significant difference between them (p>0.05). with regards to silane application in failure load shows that the mean failure load with silane increased for Voco Rebilda The mean failure load (bond strength) of Group-II-A was lower than that of Group-II-B but t-test showed that there was no significant difference between them (p>0.05).Group II (VocoRebilda DC),demonstrated greater failure load than Group I (Multilink )and Group III (RelyxU200) between the use of silanization or not. Representative samples for SEM showed ‘debonding’ mainly occurred at the dentine–cement interface. Conclusions: The results indicated that silanization of fiber posts does not make a difference to prevent dislocation of a post. Dual cure flowable adhesive composite cement was more retentive than self adhesive cements used in the study